Long-term results of surgically-assisted maxillary protraction - (:unkn) unknown (AUSTRALIAN SOC ORTHODONTISTS INC, 2014)
Objective: The long-term treatment results of surgically-assisted facemask therapy were assessed by a comparison of the immediate protraction effects with those seen at five years review. Materials and methods: Nine patients treated with a corticotomy-assisted maxillary protraction protocol were recalled five years following protraction. Cephalometric films taken before treatment (TO), immediately after maxillary protraction (T1) and five years after treatment (T2) were compared. Results: The short-term results of surgically-assisted facemask therapy showed significant skeletal and soft tissue changes. After five years, the profile and dental relationships were well maintained and a cephalometric analysis revealed a stable vertical increase but only partially maintained soft tissue changes with loss of sagittal advancement. There was significant upper incisor proclination providing dental camouflage. Conclusion: Patients who are treated with corticotomy-assisted maxillary advancement should be very carefully selected. Assessment criteria include a low mandibular plane angle Class Ill patients who have severe maxillary retrognathism unable to be treated by conventional orthopaedic correction alone; patients who have almost completed growth and missed the chance of earlier orthopaedic correction, as well as patients who are not willing to accept bimaxillary orthognothic surgery, may be successfully treated.
Keywords: RIGID EXTERNAL DISTRACTION; CLASS-III MALOCCLUSION; SKELETAL STABILITY; CLEFT-LIP; OSTEOGENESIS; EXPANSION; ADVANCEMENT; PALATE; THERAPY; DEVICE